2024
DOI: 10.3390/biomedicines12040928
|View full text |Cite
|
Sign up to set email alerts
|

Irisin and Its Role in Postmenopausal Osteoporosis and Sarcopenia

Irene Falsetti,
Gaia Palmini,
Simone Donati
et al.

Abstract: Menopause, an extremely delicate phase in a woman’s life, is characterized by a drop in estrogen levels. This decrease has been associated with the onset of several diseases, including postmenopausal osteoporosis and sarcopenia, which often coexist in the same person, leading to an increased risk of fractures, morbidity, and mortality. To date, there are no approved pharmacological treatments for sarcopenia, while not all of those approved for postmenopausal osteoporosis are beneficial to muscles. In recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Across a number of studies [recently reviewed by Falsetti et al ( 91 )] irisin levels have been found to be lowered in postmenopausal women, and across a broader range of (female and male) patients with osteoporosis irisin has often been found to correlate with bone mineral density, although this is not a consistent finding. Of particular relevance to the postmenopausal setting though, a study in OVX mice demonstrated that twice-weekly irisin administration over 5 weeks prevented the loss of trabecular bone and bone mineral density, in conjunction with greater numbers of osteoblasts ( 92 ).…”
Section: Evidence For the Mitigating Actions Of Irisin Against Compon...mentioning
confidence: 99%
“…Across a number of studies [recently reviewed by Falsetti et al ( 91 )] irisin levels have been found to be lowered in postmenopausal women, and across a broader range of (female and male) patients with osteoporosis irisin has often been found to correlate with bone mineral density, although this is not a consistent finding. Of particular relevance to the postmenopausal setting though, a study in OVX mice demonstrated that twice-weekly irisin administration over 5 weeks prevented the loss of trabecular bone and bone mineral density, in conjunction with greater numbers of osteoblasts ( 92 ).…”
Section: Evidence For the Mitigating Actions Of Irisin Against Compon...mentioning
confidence: 99%